PERCEPATAN PERENCANAAN PEMBANGUNAN SEKTOR AIR MINUM DAN SANITASI DALAM DOKUMEN PERENCANAAN DAERAH - Nora Damayanty (Journal Education and Government Wiyata, 2024)
Water is a primary human need, as is the management of waste originating from human activities. Thus, the government has a program to improve drinking water and sanitation sector. However, to develop these two sectors, a strategy is needed through preventing infrastructure, adaptation, participation, collaboration between sectors, sustainability and acceleration of development planning through the RPJMA. The aim of this study is to formulate a strategy regarding accelerating development planning for the drinking water and sanitation sector in regional planning documents. The 2020-2024 RPJMN has set targets for achieving access to adequate drinking water at 100% (including 15% access to safe drinking water), 90% access to adequate sanitation (including 15% safe access). This study was carried out by qualitative approach, and AHP method. The results of AHP processing were analyzed using a descriptive approach. Results: 1) to accelerate development planning for the drinking water and sanitation sector, a priority strategy is needed that emphasizes sustainability aspects that consistently carry out infrastructure development, especially the discovery of drinking water points, drinking water supply systems and electricity supply systems to increase the availability of water to increase drinking water sources and sanitation purposes. Sustainable planning needs to be adapted with improvements based on the principle of flexibility. For sustainable development, community participation is needed with democratic principles and collaboration between sectors using collaborative governance. Sustainable development cannot be separated from the planning document, namely the RPJMA, which is implemented with high commitment to realizing the targets that have been determined.